SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP UNTUK KEBUTUHAN OPERASIONAL DENGAN METODE AHP (STUDI KASUS: DIREKTORAT PEMBINAAN KURSUS DAN PELATIHAN KEMDIKBUD) - Sanyoto, Gathot Pujo; Handayani, Rani Irma; Widanengsih, Euis (LPPM Universitas Nusa Mandiri, 2017)
Laptop is a basic need for people, either for education or for business activities. However, choosing the right laptop according to customer needs, specifications of the laptop and the right price is not easy.One way to help the prospective buyer in order to determine a laptop that will be purchased in accordance with the requirements is the decision support system. Decision support system designed to support all stages of decision making ranging from identifying the problem, selecting the relevant data and determine the approach used in the decision making process to evaluate the alternatives that exist. The method used in this decision support system is AHP (Analytical Hierarchy Process) to assist in the selection of laptop. AHP is a method which is the main input of human perception. To complete this method, aided by application of Expert Choice 11.